A 1 Million Year Record of Biogenic Silica in the Indian Ocean Sector of the Southern Ocean: Regional Versus Global Forcing of Primary Productivity. Issue 3 (18th March 2021) - Kaiser, Emily A.; Billups, Katharina; Bradtmiller, Louisa
Abstract: A new orbital‐scale record of bulk sediment biogenic silica (opal) content from Ocean Drilling Program (ODP) Site 745B spans the past 630 kyr (Marine Isotope Stages (MIS) 1–16). Together with the published portion of the record (MIS 16–31, Billups et al., 2018), we obtain a 1 million year orbital‐scale record of paleoproductivity in the Antarctic Zone of the Indian Ocean sector of the Southern Ocean. A coherent age model is based on tuning variations in the opal content to the benthic foraminiferal δ 18 O stack of Lisiecki and Raymo (2005). Consistent with other sites from the Antarctic Zone of the Southern Ocean, we align opal maxima with interglacial and opal minima with glacial intervals. Opal variations are significant at all three primary periodicities (100, 40, and 23 kyr), coherent (>95%), and in‐phase with the tuning target on the scale of individual cycles as well as their amplitude modulation. This supports the assumption of global ice volume‐related changes in Southern Ocean paleoproductivity in the derivation of the age model. Between MIS 11 and 4, however, the opal record lacks minima corresponding to the glacial extremes of MIS 10, 8, and 6. During this interval of time, opal fluctuates primarily with a 23 kyr precession signal. We suggest that the productivity response to precession reflects an ice‐free sea surface that remains sensitive to wind‐driven upwelling of nutrients. Results from Site 745B illustrate the potential importance of regional climate forcing factors on longer time scales and their interplay with global climate background conditions. Key Points: A 1 million year composite opal record from ODP Site 745B provides evidence for orbital‐scale changes in paleoproductivity During Marine Isotope Stages 11‐4 percent opal remains relatively high, and small‐scale variations occur primarily at the 23 kyr periodicity Sensitivity to precession is a regional response to variations in wind‐driven upwelling of nutrients rather than to global climate forcing